THE APPLICATION OF THE NHT TYPE COOPERATIVE LEARNING MODEL TO IMPROVE BIOLOGY LEARNING OUTCOMES IN CLASS XI SMA NEGERI 10 MEDAN - Masnarita Girsang (Jurnal Pelita Pendidikan, 2021)
This study aims to improve student achievement by applying cooperative learning model type NHT in class XI IPA I SMA N 10 Medan. This research procedure was carried out through three cycles with four stages: planning, implementing actions, observing, and reflecting. The results showed that the actions that have been taken could improve student achievement in Biology subjects in class XI IPA I SMA N 10 Medan. It is evidenced by an increasing number of students who have passed the minimum grade. In the initial conditions, 50% to 79.10% in the first cycle increased again to 100% in the second cycle. The highest score reaches 95, and the lowest score is 70. In addition, the NHT cooperative model can increase learning motivation. Students who are characterized by increased student learning activities.